Tailoring the hydrogen storage performance of the Cr-, Mn-, and Fe-doped circumcoronenes by the presence of N and B co-dopants: Computational study. (22nd September 2022) - Malček, Michal; Čermáková, Kristína; Rapta, Peter; Gall, Marián; Bučinský, Lukáš
Abstract: Reliance of human population on quickly depleting fossil fuels stimulates a search for sustainable alternatives. Hydrogen represents one of the most promising candidates to replace the largely consumed fossil fuels. One of the crucial issues of the hydrogen cycle is the H2 gas storage under ambient conditions. Hence, a search for effective H2 storage devices is of urge importance. The H2 storage capacity of the Cr-, Mn-, and Fe-doped circumcoronenes (CCs) in the presence of N and B co-dopants is investigated at the DFT level of theory. Obtained results suggest that the presence of N co-dopants significantly enhances the affinity of the studied systems towards H2 binding, which consequently leads to improved H2 storage properties. Moreover, the presence of three N co-dopants energetically stabilizes the Cr-, Mn-, and Fe-doped CCs in their low-spin states, which are the most suitable for the H2 adsorption. In addition, the H2 adsorption performance of the Mn–3N-doped CCs can be altered by the oxidation and reduction. This finding indicates that an application of the external electric potential may control the H2 release-and-capture mechanism in Mn-doped CC storage devices. In addition, the metal-doped CC cation appears as the energetically preferred form (metal-doped CC is a strong reducing agent when compared to the ferrocene couple). Graphical abstract: Image 1 Highlights: H2 adsorption of the metal-doped CCs in the presence of N and B atoms is studied. N-doped CCs show enhanced affinity towards H2 adsorption. Best H2 storage performance is found for the Mn–3N-doped CCs. H2 adsorption of the studied CCs can be altered by their oxidation/reduction. Application of electric potential may control the H2 release-and-capture mechanism.